Evaluation of Quality of Life in Metropolitan Areas in a Developing Country Context: The Case of Tabriz, Iran - Zenouzi, Shahin Alizadeh; Teimouri, Raziyeh (Environmental Management and Sustainable Development, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In developing countries, one of the critical issues in urban planning is investigating and recognizing the quality of life (QoL) in metropolitan areas and preparing a comprehensive solution for it. Recognition of QoL indicators and evaluating their situation in different urban areas is a significant aspect of urban planning and development in metropolitan areas. The present study aims to evaluate the defined indicators of QoL in the urban areas of Tabriz Metropolis. After identifying the effective criteria, a pairwise comparison was conducted by the AHP method to find their weights. Then, ten Tabriz Municipality Districts and three towns located in the metropolitan area, including Basmenj, Sardrood, and Khosrowshahr, were ranked using the models of VIKOR, ELECTRE, and MORRIS. The results indicated that the QoL of districts 5, 2, and 9 among the municipality districts got the highest ranks and had a better situation than the other districts. On the other hand, districts 1, 4, and 6 have no good conditions in terms of QoL. Among the studied towns, Sardrood has better conditions regarding QoL than the others<strong style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">.